Comprehensive Analysis of E-Learning: Development, Comparative Implementation, and Optimization Strategies in Higher Education (Case Study of Wiralodra University) - Ayuni Sasi Kirana (Manajia: Journal of Education and Management, 2025)
This article presents a comprehensive analysis of the role of e-learning as a key pillar of education system transformation in the digital era. The study covers the historical evolution of e-learning from simple computer-based systems to globally integrated Learning Management System (LMS) platforms. A comparative analysis is conducted to identify key pedagogical differences in e-learning implementation at the school and higher education levels, where student autonomy is a key differentiator. The findings indicate that while e-learning offers significant potential in flexibility, efficiency, and accessibility, its effectiveness is significantly hampered by critical challenges such as the digital divide (unstable connections) and online pedagogical issues (lack of interaction). It is concluded that optimizing educational quality, particularly at Wiralodra University, requires an implementation strategy focused on strengthening infrastructure, intensive training for lecturers in online pedagogy, and the adoption of cutting-edge technologies (such as AI and VR) to ensure an inclusive, effective, and competitive learning system.